The effectiveness of communication, information, and education (CIE) media on balanced nutrition behavior in elementary school students at SDN Bulurokeng 1 - J, Irmawati R.; Amiruddin, Fitriyah; Toffi , Astri (Institute of Computer Science (IOCS), 2023)
Insufficient energy and protein intake below the minimum requirements is usually the beginning of nutritional problems in elementary school children. Balanced nutrition behavior needs to be applied to avoid problems by providing education through IEC media. The purpose of the study to measure the effectiveness of IEC media on increasing knowledge, attitudes, and actions regarding balanced nutrition of elementary school children at SDN Bulurokeng 1 Makassar City. This research is a quantitative study using a quasi experiment design with a one group pre-test post- test design approach. The media used for intervention is KIE media Leaflet balanced nutrition. Data normality test using Kolmogrof Smirnov with the results of data not normally distributed. Then analyzed using the Wilcoxon Signed Rank Test statistical test. The results showed that the mean value of knowledge before the intervention was 73.33 after 72.08, there was no difference before and after the intervention (p value = 0.53), the attitude before the intervention was 57.35 after 76.00, the action before the intervention was 58.3 after 75.83 there was an average increase (p Value = 0.00). The study indicated that IEC media increases attitudes and actions toward balanced nutritional behavior in elementary school pupils at SDN Bulurokeng 1.